Analisis Penanganan Longsoran Double Track Muaraenim - Muaralawai Km.398 + ½Analisis Penanganan Longsoran Double Track Muaraenim - Muaralawai Km.398 + ½ - Sularno; Hidayawan, Ahmad; Adhi, Bagas Wahyu (Universitas Veteran Bangun Nusantara, 2024)
Trains are a mode of land transportation that has special characteristics and advantages, especially in its ability to transport both passengers and goods in bulk, save energy, save space, save fuel and have a high safety factor and low pollution levels and more. efficient for long distance transportation and in city transportation. Railway transportation that serves public transportation must be safe in its operation. There is subsidence on the railway line between Muaraenim Station - Muaralawai Station. So improvements need to be made to support the smooth running of goods transportation services, especially coal in the Southern Sumatra Region. The aim of this research is to look at slope stability on the Muaraenim - Muaralawai KM.398 + 1/2 railway line using Plaxis 2D software version 22.1.0.452. In implementing the Plaxis 2D program, the Mohr-Coulomb model is used for soil. Data from the Bore Log is considered undrained, which means water cannot flow and soil permeability is considered low. Backfill soil is also treated as undrained, while Limestone uses an undrained type with low soil permeability. The soil condition is considered drained, and Limestone uses the drained type. The results of evaluating slope stability in areas experiencing land subsidence were obtained using Plaxis 0.04 cm software with a safety factor of FS 2.738. The analysis was carried out under original conditions without load.